Design and Build a Simple Durian Fruit Harvesting Tool (Durio Zibethinus Murr) - Mazidatul Faizah; Muhammad Renjis Setiawan (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Fruit picking tool is one of the equipment used to facilitate the harvesting process, in fruit picking it is necessary to choose fruit that is feasible or ready to be harvested, for example ripe durian fruit. In this study, we will conduct research on the design of a simple durian harvesting tool that is not widely known by the wider community which has the potential to be one of the tools that is needed in Jombang, precisely in Sumber Village, Wonosalam District, Jombang Regency. A simple durian harvester has a circular area of ​​60 cm, a width of 30 cm, and a height of 40 cm, all of which are made of 5 ml iron and a steel knife. This tool is operated by one person and has several components, namely consisting of songong/songkrok, knife or borer, connecting frame, and pole, each of which has a specific function. This research was conducted to facilitate durian farmers in picking durian fruit and reduce the occurrence of fruit damage at harvest and practical use.